Ecological reserves in Mexico from the perspective of sustainable marketing (Revista de Investigaciones Universidad del Quindío, 2021)
The accelerated growth of the population, the prevailing need to cover more spaces to build houses, squares and buildings has been increasing; However, green spaces, such as urban parks and ecological reserves, have been reduced or abandoned by the corresponding administrations to satisfy the needs of society, with the aim of knowing the importance of the development and conservation of Ecological Reserves or Protected Natural Areas. Looking for an advantage through ecotourism, implementing sustainable marketing strategies, a qualitative study was carried out through the reading of documents from 182 web pages of protected natural areas in Mexico, analyzing characteristics, ecosystems and facilities, deepening the documentary review in the three main Ecological reserves of Querétaro. The main findings are the lack of an adequate strategy for its resources, the low percentage of budget and investment allocated to safeguarding or improving them; making sustainable marketing very important in the management of these reserves.
Keywords: Ecological reserves; sustainable marketing; ecotourism